PENGARUH PENGELOMPOKAN KELAS (UNGGULAN DAN NON UNGGULAN) TERHADAP PRESTASI BELAJAR SISWA DI MTs MUHAMMADIYAH 3 YANGGONG PONOROGO TAHUN AJARAN 2017/2018 - Aditya Putra Perdana; Rido Kurnianto; Nurul Abidin (TARBAWI:Journal on Islamic Education, 2018)
Education is very important for children, children can get education from formal education or non formal education. School is one of place for children to get a formal education. Education in the school can increase abilitiy and achievement of children as student. School have many method to increase that, one of them by grouping class pattern. This method has been tested produce the good achievement to advance that school quality. This method also used in MTs Muhammadiyah 3 Yanggong Ponorogo. That reason who make researcher make a research in there. The goal from this research to know how strategy grouping class in MTs Muhammadiyah 3 Yanggong Ponorogo, to know student achievement based on grouping class and also to know the influence between grouping class to student achievement in there. The type of this research is quantitative research by used statistic formula. The subjek in this research is 75 student of class VIII and IX. The method of data collect that used questionnaire, interview, observation and documentation. The analysis method that used linier of regression analysis. The result of research is there are significant influence from grouping class to student achievement in superior class that showed with t value 5,251 and there are not a significant influence from grouping class to student achievement ini non superior class that showed with t value 1,538.